Global Diversity and Academic Outcomes in Culturally Responsive Transformative Teaching - Rasyada, Ahyana; Mahardiani, Lina; Fakhrudin, Isma Aziz; Rahmawati , Raisya (Jurnal Inovasi Pendidikan IPA, 2025)
This research aims to reveal the effect of applying the Culturally Responsive Transformative Teaching (CRTT) learning model on students’ global diversity character and learning achievement in the cognitive domain of science learning. This study employs a quasi-experimental design with a pretest-posttest control group. The experimental class in this research employed the CRTT learning model, while the control class utilized the discovery learning model. The population consists of class VIII students from State Junior High School (SMPN) 2 Karanganyar for the 2023/2024 academic year, comprising nine classes. Meanwhile, the research sample was selected using a cluster random sampling technique, with Class VIII B as the experimental class and Class VIII A as the control class. The research data were collected through a test, surveys, observations, and interviews. The survey data test results using the Independent T-test showed a sig value. (2-tailed) = 0.018 < 0.05. The N-gain test results from students’ cognitive assessment data showed that the N-gain value for the experimental class (0.870) was greater than that for the control class (0.364). This indicates that the application of the CRTT learning model affects students’ global diversity character and learning achievement in science.